2004
DOI: 10.1037/0882-7974.19.4.592
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E and Cognitive Performance: A Meta-Analysis.

Abstract: The epsilon4 allele of the apolipoprotein E (APOE) gene is a known risk factor for Alzheimer's disease and may also affect cognitive performance in normal aging. Evidence of the presence and magnitude of epsilon4-related cognitive deficits was examined with a meta-analysis of the available literature. Thirty-eight studies were included, and cognitive performance was collapsed into 8 domains. Results indicated significant APOE-epsilon4 group differences for global cognitive functioning, episodic memory, and exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
390
10
9

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(445 citation statements)
references
References 71 publications
36
390
10
9
Order By: Relevance
“…This finding is in agreement with previous studies reporting relations between APOE genotype and cognitive function [8,31].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This finding is in agreement with previous studies reporting relations between APOE genotype and cognitive function [8,31].…”
Section: Discussionsupporting
confidence: 94%
“…The presence of at least one apolipoprotein E (APOE) ε4 allele-another important risk factor for cardiovascular disease (CVD)-is associated with dementia and lowered levels of cognition [7,8]. While some studies have indicated that the presence of at least one APOE ε4 allele is associated with lowered cognitive performance [9,10], negative findings have been reported in a number of investigations, particularly those in which persons with dementia or preclinical dementia have been excluded from the study samples [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the presence of a 4 allele was associated with poorer performance on tests of global cognitive functioning, episodic memory and executive functioning. No differences were observed however, on tests of perceptual speed, attention, short-term memory and visuospatial skills [31]. The absence of any significant observed effects, especially in the domain of attention, was thought to relate to the use of tests that were not sensitive enough to detect subtle impairments.…”
Section: Introductionmentioning
confidence: 91%
“…Metaanalyses also suggest both 4-related cognitive deficits, and 2-related cognitive benefits, in later life (3,4). However, there is accumulating evidence that the subclinical phase of dementia precedes eventual diagnosis by several years, even decades.…”
Section: Introductionmentioning
confidence: 99%